Problems of formation of ecological networks for environmental safety of Odesa region - Чубрей, Олександра; Yavorska, V; Kolomiyets, K; Trigub, V (IV International Scientific Congress SOCIETY OF AMBIENT INTELLIGENCE 2021, 2021)
Currently, the concept of sustainable development of nature and society is gaining relevance, a key aspect of which is the development of the ecological network. In Ukraine, there is a regulatory framework for the formation of an ecological network of three levels - Pan-European, National and regional. One of the important problems is that in the developed schemes of regional eco-networks should be interconnected to the eco-networks of neighboring regions and countries. The main features of the ecological network of the Odesa region are due to its coastal position and location mainly in the Steppe, partly Forest-Steppe landscape zones. The region includes vast areas of coastal territories and coastal waters - coastal zones, which concentrate unique protected areas. Mandatory basis for the formation of ecological networks is land use. The proposed concept of geoplanning is based on planning developments of the main components of the territory: the natural environment; population; economic activity. The basic characteristics of the natural environment are the landscape map and physical and geographical zoning of the territory. Maps of resilience of the natural environment to man-caused load, natural and ecological potential of the territory, levels of ecological and economic balance have already been drawn up. This series of maps for the needs of planning the territory of Ukraine should be continued by project maps of national and regional ecological networks, as well as maps of ecological capacity of the territory for population settlement, various economic activities and the general level of economic development in general. For the needs of spatial planning it is necessary to emphasize the levels of anthropogenic and urban pressures on the natural environment in the settlement of the population. Allocation of water fund lands in kind and strict regulation of their use is the main prerequisite for the formation of ecological networks of Ukraine and its regions
Проблеми формування екологічних мереж екологічної безпеки Одеської області
Keywords: Ecological Networks; Odesa Region; Environmental Safety